ANALYSIS OF THE EFFECT OF FINANCIAL PERFORMANCE AND MARKET PERFORMANCE ON FIRM VALUE WITH MARKET VALUE ADDED AS A MEDIATION VARIABLE - Saraswati Risma Dewi; Aidilla Fitri Dwi Setyowati; Sekar Kalista; Theresia Trisanti (LPPM STIE YKPN Yogyakarta, 2023)
The purpose of this study is to determine the effect of financial performance calculated by Return on Assets and market performance calculated by Price Earning Ratio on firm value through Market Value Added as an intervening variable in mining companies listed on the Indonesia Stock Exchange in 2018-2020. The population used is 77 mining companies, purposive sampling method is used as a sampling technique which is then obtained by 25 mining companies with 75 data. Hypothesis testing uses a simultaneous test, partial test, and Sobel test. The research findings show that the relationship between financial performance and firm value; is supported, but the relationship between market performance and firm value; is not supported. Furthermore, Market Value Added can mediate the effect of financial performance on firm value, but Market Value Added is not able to mediate the effect of market performance on firm value